The Impact of Climate Change on Economic Conditions: Evidence in Indonesia - Febriandika, Nur Rizqi; Rahayu, Cahyaningtiyas (JEJAK: Jurnal Ekonomi dan Kebijakan, 2021)
Climate change has consequences and influences on agricultural productivity, especially in tropical areas such as Indonesia. Agricultural produce contributes to the level of Gross Domestic Product. Climate change is a challenge for the environment that has the most extensive impact on the economic, natural resources, and agricultural sectors, even as a concern for climate change on agricultural production. So it is needed to discuss climate change which has an impact on various sectors, especially the economic sector. This research was carried out during 2016-2018 using all provinces in Indonesia. This study uses panel data regression method, and the chosen model is the Fixed Effect Model (FEM) by displaying the effects of each region. The results of this study show that R-squared value isÂ  0.990095 which means that 99% of independent variables collectively determine the value of GDP. Meanwhile, changes in temperature, increased rainfall, and increased air quality index partially have no effect on GDP. Only the extent of agricultural land area partially has a positive effect on GDP.